2006
DOI: 10.3892/or.16.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase inhibition by an siRNA directed against hTERT leads to telomere attrition in HT29 cells

Abstract: Abstract. Human telomerase is a ribonucleoprotein complex composed of at least the reverse catalytic transcriptase hTERT and RNA component hTR. The enzyme stabilizes telomere length and thereby contributes to unlimited cell proliferation, i.e. immortality. Reactivation of telomerase activity during carcinogenesis is a common hallmark in most human tumor types. Consequently, telomerase is an attractive molecular target toward which to direct cancer therapeutic agents. RNA interference (RNAi) has been shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
0
23
1
Order By: Relevance
“…Growth evidence has demonstrated that inhibiting telomerase; especially hTERT, by genetic, antisense RNAi is a highly promising for cancer therapy as already demonstrated in several cancer cell lines (15)(16)(17)(18). Zhang et al transfected a plasmid encoding hTERT-specific shRNAs into human hepatocellular carcinoma cell lines and found that they could stably suppress hTERT expression, which led to the inhibition of cell proliferation and to an attenuated tumorigenic potency (19).…”
Section: Introductionmentioning
confidence: 99%
“…Growth evidence has demonstrated that inhibiting telomerase; especially hTERT, by genetic, antisense RNAi is a highly promising for cancer therapy as already demonstrated in several cancer cell lines (15)(16)(17)(18). Zhang et al transfected a plasmid encoding hTERT-specific shRNAs into human hepatocellular carcinoma cell lines and found that they could stably suppress hTERT expression, which led to the inhibition of cell proliferation and to an attenuated tumorigenic potency (19).…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference (RNAi ) is a novel gene therapy technology (16,17) in which 21-25 nucleotide small interfering RNA (siRNA) duplexes, homologous to the silenced gene, function as sequence-specific RNAi mediators, suppressing the expression of the target gene. siRNA synthesis in vitro is the latest development in RNAi; however, the poor stability and specificity of siRNA in vivo restricts its use (18).…”
Section: Introductionmentioning
confidence: 99%
“…undergoing deleterious degradation and fusion events (9,10). A great number of studies manifest that cellular radiosensitivity is related to the cellular reproductive ability, so there should be some kind of intrinsic correlation between the telomere length and radiosensitivity (11)(12)(13). Our previous research also indicated that radiosensitivity is negatively correlated with telomere length, the longer the telomere length, the lower the radiosensitivity (8).…”
Section: Discussionmentioning
confidence: 90%